Shelf Life and Quality Stability Determination of Drying Shredded Dumbo Catfish (Clarias Gariepinus) - Nugroho, Matheus; Susanti, Eli; Sugiono, Sugiono (Graduate School, Universitas Brawijaya, 2023)
The purpose of this study was to determine the stability of the quality and shelf life of dried shredded African catfish (Clarias gariepinus). The method used in this study was quantitative research using an experimental method using a completely randomized design with three different drying treatments. The stability of the drying quality of African catfish shredded (Clarias Gariepinus) was the color of African catfish shredded with varying methods of drying, giving panelist scores ranging from 2.36 to 4.4; organoleptic value of African catfish floss ranged from 2.88 to 4.16; panelists' assessment of the texture of African catfish shredded ranged from 2.12 - 4.56; the taste of African catfish floss ranges from 2.08 to 4.44. Shredded African catfish with different drying durations that were most in demand by panelists was sample A3 shredded African catfish steamed and dried for 4 minutes in a spinner machine with a color score of 4.4, aroma 4.16, texture 4.56, and taste 4.44. The results of measurements using distribution turnover explained that the shelf life of shredded catfish could last up to 7 months and was reduced to 6 months to anticipate product damage earlier. Keywords: quality, shelf life, shredded dumbo catfish.